The Development of Chemical Industries In the Philippine - Servillano Olano (ASEAN Journal of Chemical Engineering, 2022)
This paper attempts to briefly describe the development and state of the chemical industry in the Philippines by presenting related information reported by government agencies and practitioners specificallyby the Chemical Industries Association in the Philippines.The informationcan help describethe weaknesses,problems, development aspects, prospects, and strengths of the industry. Hopefully, with the current development and the new and vigorous thrust of the government and private sector, trends for the coming years will be bright for the chemical industry and the industrialization of the country as a whole.